Populism, propaganda, and political extremism : building the rage machine - Klein, Adam (Routledge, 2025)
At its core, this book is about political anger: how it is cultivated, where it is taking us, and how to address it. Populism, Propaganda, and Political Extremism: Building the Rage Machine explores the manufacturing of populist narratives and deployment of propaganda that together produce a state of outrage and disunity in American politics. Through chronicling these subversive communications, and the architects and influencers behind them, Adam Klein expertly deconstructs the processes that sow national division. Today, these divisive campaigns empower political extremists as they erode democratic norms.As this book uncovers the forms and functions of political ragemaking, it also offers concrete prescriptions for addressing the hostile partisanship that has consumed the national conversation. Here, history will serve as a critical guide. Counteractive narratives that emerged out of prior eras of destructive demagogues like Joseph McCarthy and George Wallace will be explored for their neutralizing potential. The book also faces down some of the most difficult questions, such as how we reach the true believers who are not really interested in resolution, and how we preserve the First Amendment while combating political extremism.Developed with the student in mind, the book's three-part focus on populism, propaganda, and political extremism offers a framework for understanding the forces behind our fractured politics-and the strategies that may counter them.
Keywords: Populism -- United States -- History.; Propaganda, American -- History.; Radicalism -- United States -- History.; Sociolinguistics -- Political aspects -- United States.; United States -- Politics and government.; elektronické knihy; electronic books